Development of Jakarta Kota Station Function From Public Transportation Facilities to Become a Historical and Cultural Tourism Destination Ariani, Atridia Wilastrina, Titien Retnoningsih, Ari Atmadja - Ariani, Ariani; Wilastrina, Atridia (Universitas Negeri Semarang, 2020)
The Jakarta Kota Station, also known as Beos Station, is one of the buildings designed by a Dutch architect full of historical value and beautiful architectural form. In addition to its main function as a railway facility, Jakarta Kota station also plays a role in the economic sector for the surrounding community. This study aims to examine and provide recommendations regarding opportunities to develop the function of Jakarta Kota station from public facilities to become historical and cultural attractions. The method of design sociology with a qualitative approach is used to analyze various aspects related to the research problems such as design connection and socio-cultural phenomena, urban society, socio-cultural changes, design and environment, design and architecture, as well as tourism and culture. Based on the results of the analysis it can be concluded that apart from being a public railway facility, Jakarta Kota station is feasible to be developed into a historical and cultural tourism destination that supports the government's goal of making the Kotatua region into a historical, cultural, business and tourism site without changing its original physical form